Knowledge gaps, sleep disturbances, and energy imbalance among female field hockey players - Puchalt-Urbano, X.; Calderón-García, A.; Huertas, J. R.; Sánchez-Oliver, A. J.; López de la Torre, C.; Aguila-Aguilar, E.; Lopez Soto, P. J.; Luque, R. M.; Mata-Ordóñez, F. (Nutrients, 2025)
Background: Field hockey is a high-intensity intermittent sport, where nutrition and sleep play an important role in the performance and health of all players, especially in women, who often exhibit a dietary pattern characterized by low energy and carbohydrate intake, along with poor nighttime habits. The purpose of this study is to evaluate the profile of female field hockey players by analyzing their energy and macronutrient intake, prevalence of LEA risk, use of SS, and sleep characteristics. Methods: A cross-sectional, observational, and descriptive study was carried out with 75 female players. Validated questionnaires were used to determine general sports nutrition knowledge (NUKYA) and specific knowledge of carbohydrates in sports (CEAC-Q), sleep quality (ASSQ), low energy availability risk (LEAF-Q), and use of sport supplements. In addition, a 7-day dietary record was analyzed. Results: Players showed a high general nutrition knowledge (NUKYA mean: 66.0 ± 8.5 points; 68.0% scored high), but a pronounced deficiency in specific carbohydrate knowledge (CEAC-Q mean: 24.3 ± 14.9 points; 84.0% scored low). Dietary intake analysis revealed significant deficiencies: mean energy intake was 31.9 ± 10.8 kcal/kg/day, resulting in insufficient intake for 78.7% of players. Carbohydrate intake was particularly low (3.6 ± 1.5 g/kg/day), with 86.7% failing to meet recommendations. Furthermore, 33.3% of players were at risk of Low Energy Availability (LEA). LEA risk (LEAF-Q score) was negatively correlated with both protein (r = -0.363; p = 0.001) and carbohydrate intake (r = -0.347; p = 0.003). Regarding sleep, the mean disturbance score (SDS) was 6.5 ± 2.9 (mild disturbance), with 33.3% showing moderate-severe disturbance, and 92.0% sleeping <=8 h. Finally, 78.7% of players used supplements, with usage correlated with CEAC-Q scores (r = 0.233; p = 0.044), and 86.4% were guided by non-professional sources. Conclusions: Female hockey players do not meet dietary recommendations for energy and carbohydrates and exhibit a high prevalence of low energy availability and sleep disturbances, despite having acceptable general sports nutrition knowledge. It is recommended to implement specific educational and nutritional strategies to enhance the knowledge, performance, and health of female hockey players.